Pengaruh Attitude, Knowledge dan Penerapan CRM terhadap Kinerja Customer Service Bank BNI Area Kalimantan Selatan - Fitri Yadi Abdis; Hairudinor Hairudinor; Noor Hidayati (Universitas Lambung Mangkurat, 2015)
This study aimed to examine the effect of Attitude, Knowledge of the application of CRM and test the effect of Attitude, Knowledge, Application of CRM on the Performance of Customer Service through a quantitative approach with methods of explanatory research, the technique of scoring using a Likert scale and the analytical techniques used is the approach of Structural Equation Model ( SEM) with Software Partial Least Square (PLS) and SPPS.Results of this study explains that the attitude variables not significant effect on CRM which the known value of the variable t <t table, namely: 1.608 <2.01, significantly influence the knowledge variable CRM variables which are known t count> t table, namely: 5.722> 2.01, attitude variables not significant effect on the performance of customer service where the variables are known values t <t table, namely: 1.708 <2.01, not significant knowledge variable to variable customer service performance which, known values of t <t tables, namely: 0.777 <2.01, while the CRM variables significantly influence the performance of a customer service where the variables are known values t <t table, namely: 9.852 <2.01.This study shows that the dimensions of knowledge have the effect of higher significance than Attitude towards CRM. Similarly, the CRM has a positive and significant impact on the performance of Customer Service.Keyword: Attitude, Knowledge, Application Performance Against CRM Customer Service